2020
DOI: 10.1115/1.4046637
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Microfluidic Flow Inside the Organ of Corti

Abstract: Abstract We study the vibration modes of a short section in the middle turn of the gerbil cochlea including both longitudinal and radial interstitial fluid spaces between the pillar cells (PC) and the sensory hair cells to determine the role of the interstitial fluid flow within the organ of corti (OoC). Three detailed finite element (FE) models of the cochlear short section (CSS) are studied. In model 1, the CSS is without fluids; model 2 includes the OoC fluid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It has been observed that electrical excitation of OHC motility causes a pumping of fluid through the SN and into the ToC, and that this possibly enhances cochlear amplification through yet-to-be discovered mechanisms (Karavitaki and Mountain, 2007). A recent FE modeling study features a representation of the gerbil mid-frequency OoC interstitial fluid spaces, and suggests that the role of the interconnected OoC fluid spaces is to redistribute pressure from OHC contractions so as to avoid excessive pressure buildup in the cortilymph space (Zagadou et al, 2020). Comparable FE studies of the high-frequency hook region are currently lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that electrical excitation of OHC motility causes a pumping of fluid through the SN and into the ToC, and that this possibly enhances cochlear amplification through yet-to-be discovered mechanisms (Karavitaki and Mountain, 2007). A recent FE modeling study features a representation of the gerbil mid-frequency OoC interstitial fluid spaces, and suggests that the role of the interconnected OoC fluid spaces is to redistribute pressure from OHC contractions so as to avoid excessive pressure buildup in the cortilymph space (Zagadou et al, 2020). Comparable FE studies of the high-frequency hook region are currently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In the middle turn of the gerbil cochlea, electrical stimulation of the OHCs has produced fluid waves in the ToC (Karavitaki and Mountain, 2007). Thus, knowledge of the OoC fluid spaces and surrounding structures is important for a full understanding of cochlear amplification (Zagadou et al, 2020). However, these fluid spaces are typically absent in histological images of the high-frequency hook region.…”
Section: Introductionmentioning
confidence: 99%
“…The boundary conditions on the basal and apical faces of the slice need to be specified. In real cochleae there is considerable motion of cochlear structures in the longitudinal direction (Karavitaki and Mountain, 2007;Wang et al, 2021), so clamping the slice faces, as was done by Zagadou et al (2020), is not realistic. Instead, we strived to capture the motion induced by the traveling wave by using a computationally-efficient "Floquet" boundary condition that mimicked how the traveling wave changed the phases of the motions at the edges of the slice.…”
Section: Wavenumber and The Floquet Methodsmentioning
confidence: 99%
“…The boundary conditions on the basal and apical faces of the slice need to be specified. In real cochleae there is considerable motion of cochlear structures in the longitudinal direction (Karavitaki and Mountain, 2007; Cooper et al 2018; Wang et al, 2021), so clamping the slice faces, as was done by Zagadou et al . (2020), is not realistic.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional two-dimensional models cannot simulate the longitudinal movement of the organ of Corti ( Cai and Chadwick, 2003 ; Cai et al, 2004 ; Ni et al, 2016 ; Steele and Puria, 2005 ). Beam models always need to simplify the geometry of the organ of Corti ( Nam, 2014 ; Nam and Fettiplace, 2010 ), but three-dimensional models could reflect more detailed physiological structures ( Zagadou et al, 2020 ). The “feedforward” models proposed by Steele et al (1993 , 1999 ) and Geisler and Sang (1995) reproduced many of the structural features but did not focus on producing the longitudinal vibration in the hotspot.…”
Section: Introductionmentioning
confidence: 99%